Vertically standing Ge nanowires on GaAs(110) substrates - Song, MS; Jung, J; Kim, Y; Wang, Y; Zou, J; Joyce, H; Gao, Q; Tan, H; Jagadish, C (2008)
The growth of epitaxial Ge nanowires is investigated on (100), (111) B and (110) GaAs substrates in the growth temperature range from 300 to 380°C. Unlike epitaxial Ge nanowires on Ge or Si substrates, Ge nanowires on GaAs substrates grow predominantly along the direction. Using this unique property, vertical Ge nanowires epitaxially grown on GaAs(110) surface are realized. In addition, these Ge nanowires exhibit minimal tapering and uniform diameters, regardless of growth temperatures, which is an advantageous property for device applications. Ge nanowires growing along the directions are particularly attractive candidates for forming nanobridge devices on conventional (100) surfaces. © IOP Publishing Ltd.